Inelastic scattering of NO by Kr: Rotational polarization over a rainbow. - Chadwick, H; Nichols, B; Gordon, S; Hornung, B; Squires, E; Brouard, M; Kłos, J; Alexander, M; Aoiz, F; Stolte, S (American Chemical Society, 2014)
We use molecular beams and ion imaging to determine quantum state resolved angular distributions of NO radicals, after inelastic collision with Kr. We also determine both the sense and the plane of rotation – the rotational orientation and alignment respectively – of the scattered NO. By full selection and then detection of the quantum parity of the NO molecule, our experiment is uniquely sensitive to quantum interference. For forward scattered NO we report hitherto unseen changes in the plane and sense of rotation with scattering angle, and show, remarkably, that the rotation of the NO molecule after collision can be near-maximally oriented for certain transitions and scattering angles. These effects are enhanced by the full parity selection in the experiment, and result from the interplay between attractive and repulsive forces.